ANALYSIS OF THE PROPERTIES OF CERTAIN STABLE ORGANIC POLLUTANTS - Bezvoziuk, Iryna; Petruk, Roman; Melnyk, Tetiana (Scientific Works of Vinnytsia National Technical University, 2015)
The paper considers the results of the analysis of stable organic pollutants, formed as a result of human activity and accumulated in Ukraine; their toxicologic characteristics have been investigated for further monitoring of these substances in Vinnytsia Region. REFERENCES 1. Державна екологічна інспекція у Вінницькій області : результати роботи [Електронний ресурс] // Режим доступу : http://vindei.gov.ua/. 2. Протокол по стійким органічним забруднювачам до конвенції 1979 року до трансграничного забруднення повітря на великі відстані : Організація обєднаних націй – 1998 р. [Електронний ресурс] The 1998 Aarhus Protocol on Persistent Organic Pollutants (POPs). / Режим доступу: http://rac.org.ua/fileadmin/user_upload/publications/IEL_Guide_final_no_cover.pdf. 3. Національний план виконання стокгольмської конвенції про стійкі органічні забруднювачі київ – 2011 зміст: [Електронний ресурс] // Режим доступу : http://govuadocs.com.ua/docs/index-19099998.html. 4. Химико-аналитические аспекты полихлорированых дибензо–пара-диоксинов и других стойких органических загрязнителей [Електронний ресурс] / Проданчук Н. Г., Чмиль В. Д. // Современные проблемы токсикологии. – 2006. – №3. – Режим доступу до журн.: http://www.medved.kiev.ua/Web_journals/Arhiv/Toxicology/2006/3_2006/str90.pdf. 5. Toxic equivalency factors (TEFs) for PCBs, PCDDs, PCDFs for humans and wildlife / Van den Berg M., Birnbaum L., Bosveld A. T. C. [et all] // Environmental Health Perspectives. – 1998. – V. 106 (12). — P. 775—792. 6. Федоров Л. А. Диоксины: химико-аналитические аспекты проблемы / Л. А. Федоров, Б. Ф. Мясоедов // Успехи химии. – 1990. – Т. 59, В. 11. – С. 1818 – 1866. 7. Гаутман З. Органическая химия / Гаутман З., Грефе Ю., Ремане Х. – М. : Химия, 1979. – 832 с. 8. Химическая энциклопедия. Т. 2. Изд. / [научно-редакционный совет А. М. Прохоров Н. И. Ефимов Р. Н. Нургалиев и др.]. – М.:"Советская энциклопедия", 1990. – С. 73. 9. Гаутман З. Органическая химия / Гаутман З., Грефе Ю., Ремане Х.; пер. с нем. П. Б. Терентьев, С. С. Чуранов. –М.: Химия, - 1979. – 832 с. 10. Клюев Н. А. Определение полихлорированных бифенилов в окружающей среде и биоте / Н. А. Клюев, Е. С. Бродский // Полихлорированные бифенилы. Супертоксиканты XXI века. – 2000. – Информ. вып. № 5. – С. 31 – 63. 11. Проект № GF/2732-03-4668. «Забезпечення заходів із розроблення Національного плану щодо впровадження у Україні Стокгольмської конвенції про стійкі органічні забруднювачі». Україна. Національний план використання Стокгольмської конвенції про стійкі органічні забруднювачі. – Київ, 2006. – 279 с. 12. Стойкие органические загрязнители экосистемы / Ранский А. П., Коваленко В. С., Ткачук М. Ф. [та ін.] // Химия и хим. технология. – 2006, - № 5. – С. 239 – 245.